Paradigma Kecerdasan Majemuk Howard Gardner: Peluang dan Tantangan dalam Pendidikan Dasar di Indonesia - Nurzaidah, Nurzaidah; Ruslaini, Ruslaini (Medan Resource Center, 2025)
The implementation of Multiple Intelligence (MI) theory in primary education offers significant potential for fostering inclusive and student-centered learning. This study explores the theoretical foundations of MI, its application in Indonesian primary education, and the challenges and opportunities it presents. MI theory, introduced by Howard Gardner, posits that intelligence comprises multiple dimensions beyond conventional IQ measures, encompassing cognitive, social, emotional, and physical aspects. This study employs a qualitative approach, analyzing the application of MI in primary school curricula and pedagogical practices. Findings indicate that MI integration enables teachers to design personalized learning strategies based on students' dominant intelligences, enhancing engagement and learning outcomes. However, challenges such as insufficient teacher training, resource constraints, and reliance on standardized assessments hinder effective implementation. Despite these obstacles, MI provides a framework for addressing student diversity and improving overall educational quality. With curriculum adjustments, targeted teacher training, and enhanced educational infrastructure, MI can serve as a transformative approach to achieving more inclusive and equitable primary education in Indonesia.